PERUBAHAN MOOD MAHASISWA PRODI KESEHATAN MASYARAKAT UNIVERSITAS UDAYANA YANG MENGGUNAKAN APLIKASI TIKTOK - Saraswati, Ni Made Prema Swari; Ekawati, Ni Komang (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT An increase in the amount of stres will reduce academic ability which affects the student's grade point average. high number of TikTok users in the millennial generation is one of the stres diversion efforts that can be made by students. The purpose of the study was to determine changes in the mood of Udayana University public health study programme students who use the TikTok application. This study uses a descriptive qualitative approach with data collection methods with in-depth interviews. Research informants are final year students of the Udayana University Public Health Study Program who are active in using TikTok . Informants were selected by purpose sampling as many 13 informants. The results showed that most of the mood changes that occurred in Udayana University Public Health Study Program students experienced changes in their mood for the better after accessing TikTok . The impact felt by informants after accessing TikTok on thesis completion efforts is also quite good. The conclusion obtained is that mood changes tend to increase, for informants who feel they are experiencing a decline in mood due to inappropriate content, they will use the swipe up or not interest feature. Students feel interested in seeing videos presented by TikTok that are short, concise and clear and have interesting content. Keywords: Change, Mood , TikTok , Unud, Bali